Chemo-selective modification of cysteine residue: synthesis and application in the discovery of potential drug candidates - Yanyan Liao; Xuefeng Jiang (Exploration of Drug Science)
Chemo-select modification of peptides, targeting a handful of the most reactive proteinogenic amino acids (AAs), is gradually utilized to address the medical needs of peptide drugs and biopharmaceuticals. Cysteine (Cys), one of the less abundant AAs in many biological proteins, plays a vital role in the catalysis, signal transduction, and redox regulation of gene expression. In natural AAs (α-AAs) residues, Cys exhibits high nucleophilicity and low redox-active potential, making it a primary target for site-selective conjugation. This review summarizes several representative Cys-peptide/protein conjugation strategies developed in recent years, including polar reactions, radical coupling reactions, and stapling techniques.